A co-additive nanoemulgel formulation of tretinoin and curcumin: Formulation and optimization - Parmita Phaugat, Suchita Nishal, Rohit Dutt, Aparna Khansili (Journal of Applied Pharmaceutical Science, 2022)
Tretinoin (TRT), a natural all-trans retinoic acid occurring retinoid metabolite, belongs to the first generation of retinoids used to treat various skin ailments, like acne vulgaris and skin ageing and psoriasis. In this study, a combination of drugs using TRT and curcumin (CUR) nanoemulsion (NE) is fabricated, and is further added to a gel formulation to boost the efficacy and stability of the topical formulation. A high-energy sonication technique was used in the NE fabrication, and optimization was carried out using the Box–Behnken design. The TRT–CUR–NEs were found to have a mean particle size, zeta potential, and PDI of 77.6 ± 2.1 nm, −20.7 ± 4.4 mV, and 0.268 ± 0.029, respectively. The optimized formulation of TRT–CUR–NE has a % entrapment efficiency of 85.92% ± 2.6% and 88.31% ± 3.2% for TRT and CUR, respectively, and a % loading efficiency of 19.6% ± 1.2% and 18.7% ± 2.5%, respectively, for TRT and CUR, respectively. The in vitro release profile displayed % cumulative drug release of 28.64% ± 0.31%, 80.32% ± 0.42%, and 89.64% ± 0.97% after 24 hours for plain gel, TRT–CUR–NE, and TRT–CUR–nanoemulgel, respectively.
Keywords: Tretinoin, curcumin, nanoemulsion, nanoemulgel, Box–Behnken design